Inhibitors of lecturer agility at private universities in Makassar City - Al Kausar Kalam; Fadliyani Nawir; Megawaty Megawaty (International Journal of Applied Finance and Business Studies, 2023)
Along with the rapid developments in the world of education, private tertiary institutions need to be able to adapt to rapid environmental changes, such as technology and increasingly fierce competition. Lecturer agility is key in ensuring private tertiary institutions can remain relevant and sustainable in dealing with these changes. This research aims to analyze the factors that hinder lecturer agility at private universities in Makassar City. Lecturer agility is the ability of individual lecturers to adapt to changes in the environment, so it is important to ensure the sustainability and success of private universities. From the extraction results in the form of a component matrix, the variable with the highest order is low level of appreciation (X13), then lack of professional development (X12), followed by lack of support from higher education leaders (X9), lack of innovation culture (X20), culture organization (X5), lack of knowledge about agility (X15), Slow organizational change (X8), Limited resources (X1), lack of access to resources (X16), Lack of support from colleagues (X14), Limited time (X18 ), lack of lecturer motivation (X10), lack of recognition of success (X17), lack of access to technology (X7), policies and regulations (X3), time constraints (X4), lack of support from family (X19), professional recognition variable, Rigid curriculum (X2), demands from students (X11) and lack of collaboration between disciplines (X6). So the opinion of PTS lecturers in the city of Makassar. regarding what factors can inhibit lecturer agility at private universities in Makassar City.